Post-Pandemic HR Trends in Romania and beyond - H. Moasa (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
Based on discussions with business leaders and managers, as well as on information provided by commercial media, in this short essay, I introduce and analyze six HR trends that will affect Romania and other countries. Ranging from issues of health and safety, meritocracy, legality, branding to issues of work migration and digitalization, these trends not only portray a possible future for organizations but also provide the necessary tools for strategy and decision making.